Two Decades of "The ALAN Review." - National Council of Teachers of English, Urbana, IL.; Kelly, Patricia P.; Small, Robert C., Jr.; National Council of Teachers of English, Urbana, IL. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1999)
Noting that "The ALAN Review" has published probing articles by and about leading authors of young adult (YA) literature and about the themes, topics, and issues at stake in YA literature, this book presents some of the best and most provocative of the essays published in "The ALAN Review" since its founding in 1974. It offers 41 essays: 25 essays feature interviews with and explorations of 8 of the finest YA authors; 16 essays look at the body of YA literature from diverse perspectives (including social and personal problems of young readers; regional literature; gender and ethnicity; and the inclusion of YA works in the English language arts curriculum); and 5 essays (not previously published) by past editors and the first and only executive secretary of ALAN, Ted Hipple. The book illuminates how "The ALAN Review" and YA literature itself have developed and come of age over the course of two decades. (RS)
Availability: National Council of Teachers of English, 1111 W. Kenyon Road, Urbana, IL 61801-1096; Web site: http://www.ncte.org (Stock No. 55448-3050: $19.95 members, $26.95 nonmembers).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adolescent Literature; Adolescents; Authors; Editors; English Curriculum; English Instruction; Ethnicity; Literary Genres; Reading Materials; Scholarly Journals; Secondary Education; Books; Collected Works, Serials